Perlindungan Hukum Perawat atas Pelimpahan Wewenang dari Dokter dalam Melakukan Tindakan Medis Jahit Luka di IGD Rumah Sakit - Khusnul Huda; Mokhamad Khoirul Huda (Jurnal Hukum dan Etika Kesehatan, 2021)
The insufficiency of medical personnel ( doctors ) incurs a situation where nurses are required to perform medical action (suturing) that is not within his domain. The action was done with or without the delegation of authority from the doktors. The characteristic issues on the delegation of authority of the medical action (suturing) to the nurses and the legal coverage for the nurses in hospital’s emergency wards. The purpose of this research is to determine the characteristics of transfer of authority to perfrom the medical action of suturing to the nurses and to ascertain legal protection for the nurses performing the action in a hospital emergencr wards. This research uses legal, conceptual and comparative approaches. This research found that there exist a regulation on the transfer of authority from doctors to nurses to perform medical action such as suturing, which are Act No. 38, 2014 on nursing and the ministry of Health’s Ordinance No. 26, 2019 on the Regulation of the Implementation of Act No.38, 2014on Nursing. In the practice, the Implementation of these regulations suffers from the lack of socialization of the rules that governs the delagation of authority. The medical action (suturing) conducted by the nurse falls on the doctor, morally and legally, since it was done on the doctor’s instruction